HUBUNGAN PENGUASAAN GAYA BAHASA DAN PENCITRAAN DENGAN KEMAMPUAN MENULIS PUISI PADA SISWA KELAS X SMA 2 PADANG CERMIN - Desnia Verlinda (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2020)
This determination aims to find out what difficulties exist in high school students, the lack of knowledge of writing is one of the great homeworks for educators especially in the Indonesian language, writing is a way to train students to create creative ways of thinking and expand vocabulary, research in writing assignments This poetry is expected to know the meaning of language style, imagery and the use of both in poetry writing, language style is semeotic in building signs in poetry, imagery is an image that builds the character of a writing so that it reaches the reader when writing poetry.